PENGARUH INTENSITAS ASET TETAP DAN RETURN ON ASSET TERHADAP TINDAKAN PENGHINDARAN PAJAK - Rusmanto -; Indra Saputra; Yudha Rusmida (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2020)
Abstract. The purpose of this study is to empirically prove the effect of fixed asset intensity and return on assets on tax avoidance in the mining and mining service sector listed on the Indonesia Stock Exchange for the 2016-2018 period. The sample in this study was obtained by purposive sampling method. "Purposive sampling is a sampling technique with certain considerations. The results of this study indicate that the Fixed Asset Intensity Variable shows the regression coefficient of 0.007 with a significant variable value of 0.578 where 0.578> 0.05 (5%) and the Return on Assets variable shows the regression coefficient of 0.003 with a variable significant value of 0.665 where 0.665> 0 , 05 (5%).